2018
DOI: 10.1101/319400
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Production of spliced long noncoding RNAs specifies regions with increased enhancer activity

Abstract: Active enhancers in mammals produce enhancer RNAs (eRNAs), that are bidirectionally transcribed, unspliced, and unstable noncoding RNAs. Enhancer regions are also enriched with long noncoding RNA (lncRNA) genes, which are typically spliced and are longer and substantially more stable than eRNAs. In order to explore the relationship between these two classes of RNAs and the implications of lncRNA transcription on enhancer functionality, we analyzed DNAse hypersensitive sites with evidence of bidirectional trans… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
57
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(64 citation statements)
references
References 74 publications
7
57
0
Order By: Relevance
“…The highly female-biased gene A1bg is nearby many lncRNAs, however, we observed that a subset of interacting lncRNAs was consistently femalebiased across different studies, experiment types, and mouse strains ( Figure S5C,D) -suggestive they may play a functional role. Currently, enhancer-associated lncRNAs are defined as those transcribed from enhancers and show interesting properties such as increased enhancer activity, tissue-specificity, and association with expression of nearby protein coding genes [78,79]. Our 4C-seq results for the A1bg enhancer suggest that this model could be extended to enhancer-interacting lncRNAs as an approach to characterize or screen for candidate functional lncRNAs.…”
Section: Matthews and Waxman -Pagementioning
confidence: 91%
“…The highly female-biased gene A1bg is nearby many lncRNAs, however, we observed that a subset of interacting lncRNAs was consistently femalebiased across different studies, experiment types, and mouse strains ( Figure S5C,D) -suggestive they may play a functional role. Currently, enhancer-associated lncRNAs are defined as those transcribed from enhancers and show interesting properties such as increased enhancer activity, tissue-specificity, and association with expression of nearby protein coding genes [78,79]. Our 4C-seq results for the A1bg enhancer suggest that this model could be extended to enhancer-interacting lncRNAs as an approach to characterize or screen for candidate functional lncRNAs.…”
Section: Matthews and Waxman -Pagementioning
confidence: 91%
“…Based on our knowledge of gene regulation in other systems, at least some of these distal accessible regions may mark enhancers of gene expression. Reports in both animal and plant systems have linked enhancers with transcription of long non-coding RNAs (lncRNAs), which have been shown to control distal gene expression in various ways [42][43][44]; e.g., aiding chromatin looping to modulate expression of adjacent or distant PCGs [45][46][47].…”
Section: Long Non-coding Rnas Associate With Accessible Chromatin In mentioning
confidence: 99%
“…These studies revealed that enhancer transcription often precedes target promoter activation (De Santa et al 2010) and is positively correlated with target gene expression (De Santa et al 2010; Kim et al 2010; Arner et al 2015). The majority [>95% (Natoli and Andrau 2012; Gil and Ulitsky 2018; Tan et al 2020)] of enhancers is transcribed bidirectionally and gives rise to relatively short single exonic RNAs that are non-polyadenylated and unstable, generally referred to as eRNAs (Kim et al 2010). The remaining enhancers transcribe enhancer-associated long noncoding RNAs [elncRNAs (Marques et al 2013; Gil and Ulitsky 2018; Tan et al 2020)] predominantly in one direction (Natoli and Andrau 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The majority [>95% (Natoli and Andrau 2012; Gil and Ulitsky 2018; Tan et al 2020)] of enhancers is transcribed bidirectionally and gives rise to relatively short single exonic RNAs that are non-polyadenylated and unstable, generally referred to as eRNAs (Kim et al 2010). The remaining enhancers transcribe enhancer-associated long noncoding RNAs [elncRNAs (Marques et al 2013; Gil and Ulitsky 2018; Tan et al 2020)] predominantly in one direction (Natoli and Andrau 2012). In contrast with eRNAs, elncRNAs are relatively stable, polyadenylated and can be spliced (Natoli and Andrau 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation